(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Flax is preferred by consumers and used widely in clothing and garments owing to its merits, such as fast moisture absorption and carry-off, natural grain, unique style, etc. While flax, as one kind of natural bast fiber, not only includes cellulose but also includes gum consisting of pectin, hemicellulose and lignin, these materials glue cellulose into stiff sheet bundle fiber, thus, gum must be removed before spinning, through retting process, therefore, retting is the treatment that degrades the pectin-rich middle lamella connecting adjacent fiber cells to release bast fibers, which is the predominant problem in preparation. The original processing of flax is dew retting, which is time-consuming and results in unstable quality of flax. Therefore, Microbe treatment of raw flax is studied in this paper. One strain of fungus screened from soil is used in experiments, and pretreatment of flax is also involved. The evaluation is based on modified Fried Test. Treated and non-treated flax is tested by infrared spectrum and X-ray diffraction. The results manifest that ammonium oxalate is an effective pretreatment chelator to remove calcium, which loosens the tight structure of gum. Therefore, the method in which raw flax is pretreated with chelator followed by treatment with fungus is feasible; furthermore, bast fiber and xylem can be separated fully in 5h.